Age estimation based on appearance of pisiform bone in selected Nepalese children of Gandaki Province Nepal - Pangeni, Roshan; Khatri, Bharat Bahadur; Subedi, Nuwadatta; Baral, Madan Prasad; Bagale, Deepak; Khanal, Gopal Prasad (Journal of Gandaki Medical College-Nepal, 2020)
Background: Age estimation is based on general physical examination, radiological examination of bones and dental examination. The appearance of ossification center of pisiform bone is one of the important evidence for estimating age among young children between nine to 13 years. The objective of this study is to estimate the age of appearance of pisiform among the Nepalese children. Materials and methods: It is a cross sectional descriptive study conducted at the department of Radiology, Pokhara Academy of Health Sciences, Western Regional Hospital on the month of July 2020. The Antero posterior view of X Rays of either hand (left or right) including the carpal bones of the patients aged seven to 15 years of 183 Nepalese children archived at the department of Radiology were taken as samples. The X rays were checked for the appearance or non appearance of Pisiform and the age of appearance analysed. Results: One hundred and twenty seven (69.40%) of total 183 cases were males and 56 (30.60%) were females. The minimum age of appearance of pisiform was 9 years in females and 10 years in males. All the subjects had pisiform bone appeared at the age of 13 years and above. Conclusion: The minimum age of appearance of Pisiform in the study subjects was 9 years in females and 10 years in males. All the cases have pisiform ossified at the age of 13 years and above.